Cardiovascular Manifestations of Inflammatory Bowel Disease: Pathogenesis, Diagnosis, and Preventive Strategies - Diana-Maria Bunu; Cristian-Eugen Timofte; Manuela Ciocoiu; Mariana Floria; Claudia-Cristina Tarniceriu; Oana-Bogdana Barboi; Daniela-Maria Tanase (Gastroenterology Research and Practice)
Inflammatory bowel disease (IBD) refers to a group of chronic inflammatory diseases that targets mainly the gastrointestinal tract. The clinical presentation of IBD includes both gastrointestinal manifestations and extraintestinal manifestations (EIM). The reported cardiovascular manifestations in IBD patients include pericarditis, myocarditis, venous and arterial thromboembolism, arrhythmias, atrioventricular block, heart failure, endocarditis, valvulopathies, and Takayasu arteritis. The aim of this article is to review the available literature about the possible pathogenic mechanisms and determine preventive measures capable of reducing the incidence and severity of the cardiovascular manifestations. In IBD patients, the incidence of cardiovascular manifestations is low, but higher than that in the general population. Therefore, clinicians should pay attention to any new modification that might indicate cardiovascular involvement in IBD patients, and they should consider chronic inflammatory diseases in patients with cardiac conditions without an evident cause. Considering the role of inflammation in the development of cardiovascular manifestations, the management should include prevention of flares and maintenance of remission for as long as possible. Preventive measures should also include active screening and strict control of the cardiovascular risk factors in all IBD patients.